2021
DOI: 10.3389/fmicb.2021.726958
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cell Wall Polysaccharide Composition and Structure Between Strains of Sporothrix schenckii and Sporothrix brasiliensis

Abstract: Sporothrix schenckii, Sporothrix brasiliensis, and Sporothrix globosa are the main causative agents of sporotrichosis, a human subcutaneous mycosis. Differences in virulence patterns are associated with each species but remain largely uncharacterized. The S. schenckii and S. brasiliensis cell wall composition and virulence are influenced by the culturing media, with little or no influence on S. globosa. By keeping constant the culturing media, we compared the cell wall composition of three S. schenckii and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The S. schenckii cell wall is composed of chitin in the innermost layer, followed by β-(1,3)and β-(1,4)-glucans, and glycoproteins at the outermost layer [14][15][16][17][18]. Among the cell wall glycoproteins, a complex named peptidorhamnomannan (PRM) was identified, and it was established that the peptide core is modified with rhamnose (33.5%), mannose (57%), and galactose (1%) [14,15,19,20], which were isolated from the yeast-like cells and culture medium [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. schenckii cell wall is composed of chitin in the innermost layer, followed by β-(1,3)and β-(1,4)-glucans, and glycoproteins at the outermost layer [14][15][16][17][18]. Among the cell wall glycoproteins, a complex named peptidorhamnomannan (PRM) was identified, and it was established that the peptide core is modified with rhamnose (33.5%), mannose (57%), and galactose (1%) [14,15,19,20], which were isolated from the yeast-like cells and culture medium [19].…”
Section: Introductionmentioning
confidence: 99%
“…and Pseudallescheria boydii; in the latter, it was also found as part of PRM [17,29]. In S. schenckii, it was recently shown that cell wall rhamnose content correlates with virulence [18,30], and the absence of this monosaccharide affects cell wall composition and organization and interaction with innate immune cells in a TLR4-dependent mechanism [30]. On the other hand, it was proposed that PRM is recognized by cytokine modulated Ca 2+ -dependent cell adhesion molecules [31].…”
Section: Introductionmentioning
confidence: 99%
“…The S. schenckii and S. brasiliensis cell walls have been thoroughly studied and it is known that chitin is found in the inner layer, followed by β-1,3- and β-1,6-glucans surrounded by peptidorhamnomannan fibrils in the outer layer. 26 , 37 , 38 The S. globosa cell wall composition is not well studied, but it has been reported that it shows lower rhamnose, mannose, and O - and N -linked glycans content than S. schenckii and S. brasiliensis , but similar levels of glucosamine. 32 Moreover, it was also observed that even when S. globosa was grown under carbon and nitrogen limitation, the cell wall rhamnose, glucose, glucosamine, and mannose content did not change, at a difference of S. schenckii and S. brasiliensis , suggesting species-specific metabolic plasticity.…”
Section: Fundamental Aspects Of Sporothrix Globosamentioning
confidence: 99%
“…These cell wall changes led to abnormal proinflammatory and anti-inflammatory cytokine stimulation by human peripheral blood mononuclear cells, increased uptake by human monocyte-derived macrophages, and reduced ability to kill the alternative host Galleria mellonella [ 24 ]. Even though the role of rhamnose-containing glycoconjugates has not been addressed in other Sporothrix species, this monosaccharide is found in the cell wall of Sporothrix brasiliensis and Sporothrix globosa [ 10 , 14 , 15 , 27 ], and a correlation between the glucan-rhamnose ration and virulence has been proposed at least for S. schenckii and S. brasiliensis [ 27 ]. This organism is the etiological agent of human and animal sporotrichosis and belongs to a handful of medically relevant fungal species that contain rhamnose at the cell wall [ 10 , 14 , 18 , 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%